The effects of social situation cues and negative smoking outcome expectancies on attentional bias among smokers - Lin, Danling; Fan, Yumeng; Wang, Jia; Chen, Lin; Chen, Haide (Frontiers in Psychiatry, 2025)
IntroductionAlthough numerous findings support the triggering effect of drug-related cues on drug-seeking behavior among addicts, there is a paucity of studies investigating whether attentional bias toward these cues can be moderated by social factors. The present study aimed to examine the influence of social situation cues and negative smoking outcome expectancies on attentional bias among smokers.MethodsIn study 1, 36 smokers and 34 nonsmokers completed a modified dot-probe task that incorporated social situation cues as priming stimuli. In study 2 (N = 58), a sentence construction task was introduced to further explore how negative smoking outcome expectancies affect attentional bias influenced by social situation cues.ResultsStudy 1 found that attentional bias toward smoking-related cues was more pronounced in the smoking social situation cue condition than in the non-smoking social situation cue condition. Study 2 further found that when negative smoking outcome expectancies were activated, attentional bias toward smoking-related cues might be reduced in the smoking social situation cue condition.DiscussionThese results indicated that attentional bias could be sharpened not only by social situation cues but also by negative smoking outcome expectancies. This study provides preliminary evidence concerning the potential flexibility of attentional biases toward drug-related cues among individuals facing addiction issues.